Crónicas de la Guerra Civil : un poeta en el frente / Miguel Hernández ; [prólogo, Luis García Montero ; edición y notas, Editorial Sol 90] - García Montero, Luis (1958-); Hernández, Miguel (1910-1942)
Bibliografía: p. 156